Strengthening the Role of Family in the Management of Pressure Ulcers in Stroke Patients at Grandmed Hospital, Lubuk Pakam - Wati, Syatria; Fauzan, Yovi; Ginting, Samuel; Simarmata, Pratiwi Christa; Sitepu, Debi Dinha Octora (JURNAL PENGMAS KESTRA (JPK), 2025)
Stroke is a type of catastrophic illness characterized by high incidence and disability rates. It significantly impairs physical function and increases the risk of developing pressure ulcers. Pressure ulcers, or decubitus ulcers, occur due to prolonged pressure, friction, and moisture exposure, leading to skin tissue damage in areas of the body that bear weight during periods of immobility. Family support plays a crucial role in the rehabilitation of stroke patients, particularly in providing basic care, assisting with mobility, and preventing complications. This community engagement program (PkM) aimed to enhance family capacity in managing pressure ulcers through educational and practical interventions. Family involvement was facilitated through structured education and hands-on training to encourage active participation in supporting comprehensive patient recovery. The PkM activities were delivered using an educational and participatory approach to 25 participants, all of whom were family members of stroke patients currently hospitalized at Grandmed Hospital, Lubuk Pakam. The program implementation consisted of four stages: preparation, sample selection, execution, and evaluation. The results showed a significant improvement in participants’ knowledge, with an average increase of 32.6 points (59.1%) regarding the role of families in pressure ulcer care. Additionally, 92% of participants demonstrated competency in performing basic stroke care, and 96% expressed high satisfaction with the program. This PkM initiative effectively strengthened the role of families in managing pressure ulcers in stroke patients, thereby contributing to increased patient motivation and improved quality of life.